Pengaruh Desain Keamasan dan Kualitas Produk terhadap Kepuasan Pelanggan pada Home Industry Snack 324 - Sifa Novianti; Gian Fitralisma; Ellin Herlina (MAMEN: Jurnal Manajemen, 2024)
The objectives of this research are to ascertain the following: the impact of product quality on customer satisfaction; the impact of packaging design on customer satisfaction; and the combined effect of packaging design and product quality on customer satisfaction. The study's sample consisted of 96 respondents in total, and it used a quantitative descriptive technique. The following conclusions were drawn from the study's findings: The significance level is 0.00 <0.05 (below the threshold of 0.05), and the alternative hypothesis (Ha) is accepted whereas the null hypothesis (H0) is rejected since 10.491> 1.661. The Packaging Design variable (X1) of 86.4% (0.864) in Home Industry Snack 324 demonstrates a positive and significant impact on consumer satisfaction. The same goes for Ha and H0; if the result is more than 1.661 and the significance level is 0.00 <0.05 (below the threshold of 0.05), then Ha is accepted. Product Quality (X2) has a positive and significant association with Customer Satisfaction in the Household Snack Industry 324, contributing 73.3% (0.733) to it. Furthermore, customer satisfaction (Y) is positively and significantly influenced by both packaging design (X1) and product quality (X2), with a determination coefficient of 0.875, or 87.5%. The estimated values concurrently exceed the ftable limit (333.246 > 3.09) at a significance level of less than 0.05 (0.000 < 0.05).